Improving Stroke Care in Times of the COVID-19 Pandemic Through Simulation: Practice Your Protocols!. Issue 7 (July 2020) - Kurz, Martin W.; Ospel, Johanna Maria; Daehli Kurz, Kathinka; Goyal, Mayank
Abstract : During the coronavirus disease 2019 (COVID-19) pandemic, infectious disease control is of utmost importance in acute stroke treatment. This is a new situation for most stroke teams that often leads to uncertainty among physicians, nurses, and technicians who are in immediate contact with patients. The situation is made even more complicated by numerous new regulations and protocols that are released in rapid succession. Herein, we are describing our experience with simulation training for COVID-19 stroke treatment protocols. One week of simulation training allowed us to identify numerous latent safety threats and to adjust our institution-specific protocols to mitigate them. It also helped our physicians and nurses to practice relevant tasks and behavioral patterns (eg, proper donning and doffing PPE, where to dispose potentially contaminated equipment) to minimize their infectious exposure and to adapt to the new situation. We therefore strongly encourage other hospitals to adopt simulation training to prepare their medical teams for code strokes during the COVID-19 pandemic. Abstract : Supplemental Digital Content is available in the text.